Fused tetracyclic tris[1, 2, 4]triazolo[1, 3, 5]triazine as a novel rigid electron acceptor for efficient thermally activated delayed fluorescence emitters. Issue 26 (20th April 2020) - Pathak, Suraj Kumar; Xiang, Yepeng; Huang, Manli; Huang, Taian; Cao, Xiaosong; Liu, He; Xie, Guohua; Yang, Chuluo
Abstract : Tris[1, 2, 4]triazolo[1, 3, 5]triazine, a new acceptor based on a fused triazole and triazine moiety, has been utilized to construct two new star-shaped TADF emitters. Abstract : Tris[1, 2, 4]triazolo[1, 3, 5]triazine, a new acceptor based on a fused triazole and triazine moiety, is utilized to construct D3 –A star-shaped tristriazolotriazine derivatives, named 3, 7, 11-tris(4-(10 H -phenoxazin-10 yl)phenyl)tris([1, 2, 4]triazolo)[1, 3, 5]triazine (TTT-PXZ ) and 3, 7, 11-tris(4-(9, 9-dimethylacridin-10(9 H )yl)phenyl)tris([1, 2, 4])triazolo[1, 3, 5]triazine (TTT-DMAC ). Both TTT-PXZ and TTT-DMAC emitters feature TADF activities and AIEE properties. Consequently, solution processed OLEDs based on TTT-PXZ green emitters exhibited good performances, with an external quantum efficiency (EQE) of up to 6.2%.